Política e educação no Estado de São Paulo (1963-1964): a gestão do secretário Januário Baleeiro - Carvalho, Samuel José de (2018)
This dissertation examines the political performance of Father Januário Baleeiro de Jesus e Silva (1922-1991) in conducting the Secretary of the Business of Education of the state of São Paulo between February 1963 and March 1964. Amazonense, military chaplain of Aeronautics, founder of a religious congregation and some educational establishments in Minas Gerais, Baleeiro was strange to the paulista medium and assumes the invitation of Governor Adhemar de Barros, in a populist context and of significant experiences in popular education. In its management, it decrees the creation of almost a hundred schools, deploys the State Department of Scholarships, expands the education system by radio and television and installs the State Council of Education. It is considered, in the analysis, the trajectory, its networks of relations and the actions of government in which it was protagonist, against the political-social tensions of that historical moment. The research investigated in the archive of the religious institute he founded, in the laws, decrees and acts that he signed, and in the periodic press the teaching project that he defended, analyzed in the light of the notions of the research of Jean François Sirinelli on the intellectuals. The research allowed to perceive the populist, catholic and developmental character implied in the projects and actions of the paulista government, which intended to use the state as the propulsion force of national development